Three Factors of the Intrasexual Competition Scale? - Fernandez-Tapia, A (Elsevier Ltd, 2023)
In a multinational project (N = 3707), we factor analyzed a commonly used self-report measure of intrasexual competition and found a three-dimensional system. We called these factors envy (i.e., wanting what others have), jealousy (i.e., protecting what one has), and competitiveness (i.e., beliefs that one is better). To better understand these factors and test whether the solution is sensible, we examined sex differences and correlations with the Dark Triad traits (i.e., psychopathy, narcissism, and Machiavellianism), life history strategies, and age. Results are discussed using an adaptationist lens. © 2023